2006
DOI: 10.2459/01.jcm.0000199792.32479.ce
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial preconditioning and cardioprotection by volatile anaesthetics

Abstract: The biological bases and the clinical applications of ischaemic and anaesthetic preconditioning are reviewed. Ischaemic preconditioning is an endogenous defensive phenomenon of the myocardium in which brief periods of ischaemia followed by reperfusion reduce the infarct size induced by longer ischaemic stimuli; both an early and a late phase may be distinguished. In the early phase, the mediators released activate ATP-dependent potassium channels and kinase cascade; these enzymes migrating at the level of vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 97 publications
0
9
0
Order By: Relevance
“…In addition, volatile anesthetics modulate ATP-sensitive potassium channel activity [32,33], the generation of reactive oxygen species, and mitochondrial permeability transition pore opening [36]. Of note, many of those signaling molecules and effector systems can either interact directly with the scaffolding domain of caveolin or are known to localize to caveolae [16,17,37].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, volatile anesthetics modulate ATP-sensitive potassium channel activity [32,33], the generation of reactive oxygen species, and mitochondrial permeability transition pore opening [36]. Of note, many of those signaling molecules and effector systems can either interact directly with the scaffolding domain of caveolin or are known to localize to caveolae [16,17,37].…”
Section: Discussionmentioning
confidence: 99%
“…Cardiac myocytes (CM) express the muscle-specific isoform caveolin-3 [12] while other cell types in the heart express caveolin-1 and -2. Recent studies have shown: 1) the presence and interaction of all three caveolin isoforms in adult cardiac myocytes [13,14], 2) a signaling role for caveolin-1 in cardiac myocytes [15], and 3) that caveolins can scaffold proteins associated with cardiac protection [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…133 Volatile anesthetics (sevoflurane, isoflurane, and desflurane) have, in several experimental and clinical settings, been shown to protect the heart from I/R injury. [134][135][136][137] Recently, isoflurane was demonstrated to have a similar effect on the rat liver, 138 and sevoflurane, in a prospective randomized study, protected the human liver from I/R injury during liver resection. 139 It is our practice to administer volatile anesthetics at least during the last 30 min before aortic cross clamping.…”
Section: Pulmonary Carementioning
confidence: 99%
“…Delayed anaesthetic preconditioning, defined as an I/R injury limiting effect 24-72 h after the initial anaesthetic exposure, has been demonstrated in multiple models [16,17] and appears to share many of the mechanisms of early anaesthetic preconditioning [18,19]. Although not demonstrated with anaesthetic preconditioning, other models of preconditioning have shown increased activation of NF-kB by a preconditioning stimulus [12,[20][21][22] and decreased NF-kB activity following renal and cardiac I/R [23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%